Quantification of Perfluorooctanesulfonic Acid in Human Serum Using Triple Quadrupole Liquid Chromatography‒Mass Spectrometry - Abdullah Soheimi, Siti Suhana; Said, Siti Nur Faridatul Asyikin; Abdul Rahman, Amirah; Ibrahim, Effendi; Abd Latip, Normala; Sheikh Abdul Kadir, Siti Hamimah (Journal of Science and Technology, 2025)
Perfluorooctanesulfonic acid (PFOS), a persistent organic pollutant, has an unclear association with metabolic syndrome (MetS), particularly in Southeast Asian populations. Given the lack of PFOS detection in Malaysia, this study's rationale was to develop a simpler, faster, and cost-effective analytical method. We developed and validated a simple, sensitive LC-MS/MS method for PFOS quantification in human serum. The method employed an optimized Liquid-Liquid Extraction (LLE) using formic acid, acetonitrile, and n-hexane. PFOS and its internal standard were quantified using LC-MS/MS 6490 QQQ in multiple reaction monitoring (MRM) mode. The assay showed high specificity, acceptable precision, accuracy, and recovery, with a linear calibration range of 20–500 ng/mL. The validated method was used to determine PFOS level in serum from 40 healthy controls and 40 MetS patients. PFOS was detected in four MetS samples but not in any control samples. However, no significant difference was observed between the two groups (p-value = 0.1156). A sensitive and robust LC-MS/MS method for PFOS quantification was successfully developed. The preliminary detection of PFOS in a subset of MetS patients, even without statistical significance, highlights the need for larger cohort studies and further investigation into individual MetS components to fully elucidate any potential association.